Power-rate-distortion model for low-complexity video coding - Li-Wei Kang; Chun-Shien Lu (2009 Picture Coding Symposium, 2009)
Wireless visual sensor networks are potentially applicable for several emerging applications. Since the resource-limited restriction for a visual sensor node (VSN), efficient resource allocation for video compression is challenging. In this paper, a power-rate-distortion (PRD) model-based low-complexity multiview video codec is proposed. Our PRD model is used to characterize the relationship between the available resources and the RD performance of our video codec. More specifically, an RD function in terms of the percentages for different coding modes of blocks and the target bit rate under the available resource constraints is derived for optimal coding mode decision. Analytic and simulation results are provided to verify the resource scalability and accuracy of our PRD model in facilitating our low-complexity multiview video codec to achieve good performance.